The common pathophysiology between migraine and cluster headache: a literature update - Santos, Leonardo Elias Araujo Dos; Melo, Leonardo José Rodrigues de Araújo; Rodrigues, Pedro Vitor Ferreira; Parente, Ana Cecilia Neves Rios; Santos, Ana Luiza Souza; Nunes, Leslie Mateus de Sousa; Ponte, Cássia Caroline Aguiar da; Castro, Júlia Viana De; Lima, Pedro Lucas Grangeiro de Sá Barreto; Vasconcelos, Sophia Costa; Ribeiro, Rodrigo Mariano; Lucas Frigo; et al. (Headache Medicine, 2023)
Full abstract in PDF.